Safety and immunogenicity of a candidate bioconjugate vaccine against Shigella dysenteriae type 1 administered to healthy adults: A single blind, partially randomized Phase I study. Issue 36 (26th August 2015) - Hatz, Christoph F.R; Bally, Bettina; Rohrer, Susanne; Steffen, Robert; Kramme, Stefanie; Siegrist, Claire-Anne; Wacker, Michael; Alaimo, Cristina; Fonck, Veronica Gambillara
Abstract: Background: Shigellae cause severe disease in endemic countries, especially in children. Several efficacy trials have been conducted with candidate vaccines against Shigellae, but the lack of protection, the safety concerns, or manufacturing challenges hindered successful market approval. Conjugated vaccines have been shown to be safe and effective for different pathogens ( i.e., Neisseria meningitidis, Shigella pneumonia, Haemophilus influenzae ). The bio-conjugation technology, exploited here for the Shigella dysenteriae candidate vaccine, offers a novel and potentially simpler way to develop and produce vaccines against one of the major causes of morbidity and mortality in developing countries. Methods: A novel S. dysenteriae bioconjugate vaccine (GVXN SD133) made of the polysaccharide component of the Shigella O1 lipopolysaccharide, conjugated to the exotoxin protein A of Pseudomonas aeruginosa (EPA), was evaluated for immunogenicity and safety in healthy adults in a single blind, partially randomized Phase I study. Forty subjects (10 in each dose group; 2 μg or 10 μg with or without aluminium adjuvant) received two injections 60 days apart and were followed-up for 150 days. Results: Both doses and formulations were well tolerated; the safety and reactogenicity profiles were consistent with that of other conjugated vaccines, adjuvanted or not, independent of the dose and the number of injections. The GVXN SD133 vaccine elicited statistically significant O1 specific humoral responses at all time points in all vaccination groups. Between-group comparisons did not show statistically significant differences in geometric mean titers of immunoglobulin G and A at any post-vaccination time point. Conclusions: This study demonstrated that the GVXN SD133 vaccine has a satisfactory safety profile. It elicited a significant humoral response to Shigella O1 polysaccharides at all doses tested. The protein carrier also elicited functional antibodies, showing the technology's advantages in preserving both sugar and conjugated protein epitopes. This trial is registered at ClinicalTrials.gov (NCT01069471).